Functional Characterization of Water Transport and Cellular Localization of Three Aquaporin Paralogs in the Salmonid Intestine - Madsen, Steffen S.; Olesen, Jesper H.; Bedal, Konstanze; Engelund, Morten B.; Santamarìa, Yohana V.; Tipsmark, Christian K. (Frontiers in Physiology, 2011)
Intestinal water absorption is greatly enhanced in salmonids upon acclimation from freshwater (FW) to seawater (SW); however, the molecular mechanism for water transport is unknown. We conducted a pharmacological characterization of water absorption in the rainbow trout intestine along with an investigation of the distribution and cellular localization of 3 aquaporins (Aqp1aa, -1ab and -8ab) in pyloric caeca, middle (M) and posterior (P) intestine of the Atlantic salmon. In vitro iso-osmotic water absorption (Jv) was higher in SW than FW-trout and was inhibited by (mmol L-1): 0.1 KCN (41%), 0.1 ouabain (72%) and 0.1 bumetanide (82%) suggesting that active transport, Na+,K+-ATPase and Na+,K+,2Cl--cotransport are involved in establishing the driving gradient for water transport. Jv was also inhibited by 1 mmol L-1 HgCl2, serosally (23% in M and 44% in P), mucosally (27% in M) or both (61% in M and 58% in P), suggesting involvement of both apical and basolateral aquaporins in water transport. The inhibition was antagonized by 5 mmol L-1 mercaptoethanol. By comparison, 10 mmol L-1 mucosal tetraethylammonium, an inhibitor of certain aquaporins, inhibited Jv by 20%. In the presence of glucose, mucosal addition of phloridzin inhibited water transport by 20%, suggesting that water transport is partially linked to the Na+-glucose cotransporter. Using polyclonal antibodies against salmon Aqp1aa, -1ab and -8ab, we detected Aqp1aa, and -1ab immunoreactivity in the brush border and sub-apical region of enterocytes in all intestinal segments. The Aqp8ab antibody showed a particularly strong immunoreaction in the brush border and sub-apical region of enterocytes throughout the intestine and also stained lateral membranes and peri-nuclear regions though at lower intensity. The present localization of 3 aquaporins in both apical and lateral membranes of salmonid enterocytes facilitates a model for transcellular water transport in the intestine of SW-acclimated salmonids.